2013
DOI: 10.1093/icvts/ivs570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of donor–recipient gender mismatch on graft function and survival following lung transplantation†

Abstract: Donor-recipient gender mismatch does not have a negative impact on early graft function and mortality following lung transplantation. There is a trend towards a survival benefit for female recipients, irrespective of the donor gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…In female recipients of a heart transplant or a lung transplant, a survival advantage over male recipients has been noted (although that advantage is largely accounted for by the negative influence of female‐to‐male mismatches) . In the field of lung transplantation, several, but not all, authors have observed a survival advantage for female recipients . As noted above, Gries and colleagues—in their review of a large ISHLT registry of 18 072 patients, mostly in the pre‐LAS era—found no overall gender differences in survival .…”
Section: Discussionmentioning
confidence: 99%
“…In female recipients of a heart transplant or a lung transplant, a survival advantage over male recipients has been noted (although that advantage is largely accounted for by the negative influence of female‐to‐male mismatches) . In the field of lung transplantation, several, but not all, authors have observed a survival advantage for female recipients . As noted above, Gries and colleagues—in their review of a large ISHLT registry of 18 072 patients, mostly in the pre‐LAS era—found no overall gender differences in survival .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lack of significant effect of donor-recipient gender mismatch has also been observed in several other studies. [14,24,25] However, these studies did not limit the analysis to CF patients nor do a sub-analysis of those with CF. In general, in most of these studies, CF patients constituted approximately 15% of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…However, sex affects lung size independent of height (4,5,7). Furthermore, in a study in which donor lungs were allocated for transplantation via a mechanism of acceptable pTLC ratios rather than acceptable height ranges, sex did not predict survival (31,32). Worse survival in the setting of a female donor-to-male recipient sex mismatch has been reported in several studies (2,3).…”
Section: Original Researchmentioning
confidence: 98%